2013
DOI: 10.2527/jas.2013-6538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute heat stress on gene expression of brain–gut neuropeptides in broiler chickens (Gallus gallus domesticus)1

Abstract: Heat stress-induced reduction in feed intake is an annoyance of the poultry industry. Feed intake is regulated by complex mechanisms in which brain-gut neuropeptides are involved, but the changes in such neuropeptides in broiler chickens during heat exposure remain unclear. In this study, we investigated the effects of acute heat stress (35°C, 6 h, and 65% relative humidity) on the gene expression of appetite-regulating peptides in the hypothalamus and gastrointestinal tract of broiler chickens at 42 d of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 35 publications
(40 reference statements)
3
23
0
1
Order By: Relevance
“…Animal feeding behaviour is regulated by peripheral and central feeding signals (Lenard and Berthoud 2008). HS was reported to reduce FI by regulating the gene expression of brain-gut neuropeptides (Song et al 2012;Lei et al 2013). However, the possible roles of intestinal micro-organisms had always been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Animal feeding behaviour is regulated by peripheral and central feeding signals (Lenard and Berthoud 2008). HS was reported to reduce FI by regulating the gene expression of brain-gut neuropeptides (Song et al 2012;Lei et al 2013). However, the possible roles of intestinal micro-organisms had always been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that animals reduce FI to reduce metabolic heat production as this has been shown in previous research (Renaudeau et al, 2013) and that neuropeptide secretions from the hypothalamus and intestines may also be involved. Previous studies in heat-stressed broilers found that mRNA levels of ghrelin increased in the stomach and intestines after acute HS, together with a decrease in CCK mRNA abundance in the duodenum and hypothalamus (Song et al, 2012;Lei et al, 2013). The reduction in FI due to HS may be mediated mainly by activation of peripheral ghrelin secretion (Lei et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in heat-stressed broilers found that mRNA levels of ghrelin increased in the stomach and intestines after acute HS, together with a decrease in CCK mRNA abundance in the duodenum and hypothalamus (Song et al, 2012;Lei et al, 2013). The reduction in FI due to HS may be mediated mainly by activation of peripheral ghrelin secretion (Lei et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This may compromise the health and productivity of birds because these extremes considerably decrease poultry production due to reduced food intake and nutrient utilisation (Rhoads et al 2013). Also, brain-gut neuropeptides which regulate food intake are altered by heat stress, leading to decreased feed consumption (Lei et al 2013). Heat stress diminishes broiler performance and breast yield (Oliveira et al 2013); it also exerts adverse effects on the immune system, activating the central nervous system and increasing corticosterone levels, which decreases the body immune system and, increases susceptibility to Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%